The impact of community-based, peer-led sexual and reproductive health services on knowledge of HIV status among adolescents and young people aged 15 to 24 in Lusaka, Zambia: The Yathu Yathu cluster-randomised trial. - Bernadette Hensen; Sian Floyd; Mwelwa M Phiri; Ab Schaap; Lucheka Sigande; Melvin Simuyaba; Lawrence Mwenge; Rosemary Zulu-Phiri; Louis Mwape; Sarah Fidler; Richard Hayes; Musonda Simwinga; et al. (PLoS Medicine)
Background The growing population of adolescents and young people (AYP) aged 15 to 24 in sub-Saharan Africa face a high burden of HIV in many settings. Unintended pregnancies among adolescent girls in the region remain high. Nonetheless, the sexual and reproductive health (SRH) service needs of AYP have remained underserved. We conducted a cluster-randomised trial (CRT) to estimate the impact of community-based, peer-led SRH service provision on knowledge of HIV status and other SRH outcomes, including met need for contraceptives. Methods and findings Yathu Yathu was a cluster-randomised trial (CRT) conducted from 2019 to 2021 in 2 urban communities in Lusaka, Zambia. The communities were divided into 20 zones (approximately 2,350 AYP/zone) that were randomly allocated to the Yathu Yathu intervention or control arm. In each intervention zone, a community-based hub, staffed by peer support workers, was established to provide SRH services. In 2019, a census was conducted in all zones; all consenting AYP aged 15 to 24 were given a Yathu Yathu card, which allowed them to accrue points for accessing SRH services at the hub and health facility (intervention arm) or the health facility only (control arm). Points could be exchanged for rewards, thus acting as an incentive to use SRH services in both arms. We conducted a cross-sectional survey in 2021 to estimate the impact of Yathu Yathu on the primary outcome: knowledge of HIV status (self-reporting living with HIV or HIV testing in the last 12 months) and secondary outcomes, including use of pre-exposure prophylaxis (PrEP) in the last 12 months, current use of antiretroviral therapy (ART), and met need for contraceptive services. The sampling was stratified on sex and age group, and we analysed data at cluster-level using a two-stage process recommended for CRTs with <15 clusters/arm. A total of 1,989 AYP consented to participate in the survey (50% male); consent was similar across arms (63% consent/arm). Across zones, knowledge of HIV status ranged from 63.6% to 81.2% in intervention zones and 35.4% to 63.0% in control zones. Adjusting for age, sex, and community, knowledge of HIV status was higher in the intervention arm compared to control (73.3% versus 48.4%, respectively, adjusted prevalence ratio (PR) 1.53 95% CI 1.36, 1.72; p < 0.001). By age and sex, results were similar. There was no evidence for impact on any secondary outcomes, including current use of ART and met need for contraceptives. There were no adverse events reported in either arm. A key limitation of our trial is that approximately 35% of the AYP randomly selected for participation in the endline survey could not be reached. Conclusions Delivering community-based, peer-led SRH services increased knowledge of HIV status among AYP, both males and females, compared with the control arm. Scaling up the highly effective Yathu Yathu strategy has the potential to make a substantial contribution to increasing access to HIV prevention and care services for young people. However, additional implementation research is needed to understand how to improve uptake of broader SRH services, beyond uptake of HIV testing. Trial registration ISRCTN75609016, clinicaltrials.gov number NCT04060420.